Pathways to Prison: Life Histories of Former Clients of the Child Welfare and Juvenile Justice Systems - Kapp, Stephen A. (2000)
This study examines the relationship between child maltreatment and future offending from the viewpoint of former clients. Imprisoned adults describe their experiences in child welfare and juvenile justice system services. Specifically, those placed out of the home originally into the child welfare system have a different perspective on their path to prison than those placed into the juvenile justice system as delinquents. The study contributes to the literature by examining the relationship between the services children receive in the child welfare system as well as the juvenile justice system and their imprisonment as adults from a former service recipient's point of view